4 - Le développement du capital-risque peut-il bénéficier aux petites et moyennes entreprises camerounaises ? - Taka, Dieudonné (Africa Development, 2021)
As in most African counties, the importance and the growth of the small and Medium size enterprises weight (SMSE) in the Cameroonian productive apparatus is not to be demonstrated. Meanwhile, this type of enterprise is actually facing a serious financing problem. In fact, over the advanced classical reason to explain the refusal of borrow to these enterprises, Banks have become afraid due to the recent crisis of the financial system, and submit any SMSE, candidate to any bank borrow, to enormous conditions that she can not satisfy. Also, in an environment where there is no specialised structure, no organised financial market, the question of other sources of financing becomes important. This article propose as alternative solution, the capital risk and research to put at side all the insufficiencies which oppose to it development and disturbs it to play its role.